Analysis of The Influence of Regional Original Income, General Allocation Funds, Special Allocation Funds on Regional Expenditure in Kediri District, 2018 – 2022 - Paradita, Bella; Sari, Kholidah Zia Ambar; Prasetyo, Eko (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : to determine the influence of Original Regional Income, Allocation Funds General, Special Allocation Funds for Regional Expenditures in Kediri Regency, East Java Province, 2018 – 2022 Budget Year. Design/Methode/Approach : quantitative research with statistical analysis. Research Finding : The results of partial test research show that Regional Original Income has a significant influence on Regional Expenditures. in the partial test for General Allocation Funds, Special Allocation Fund do not have a significant effect on Regional Expenditures. Theoretical contribution/Originality : Stewardship Theory and Fiscal Decentralization Theory. Practitionel/Policy implication : shows that Regional Original Income is the only independent variable that has a significant effect on the dependent variable, namely Regional Expenditures. Research limitation : The influence of Regional Original Income, General Allocation Funds, Special Allocation Funds on Regional Expenditures individually and simultaneously.